Accountability of Perfomance Services of KTP-EL at The Population and Civil Registration of Langkat District - Khairunnisa Asri; Juliana Nasution (Universitas Muhammadiyah Makassar, 2022)
According to Arja Sadjiarto the concept of ''accountability' is a measurement of a performance that is carried out on organizations and individuals to fulfill the basic elements of the realization of good governance that is carried out in Indonesia, with accountability to determine the assessment of performance accountability in public services which is reviewed for quality, openness. and convenience in serving the community, the availability of means of empathy and responsiveness, a sense of security and comfort,'' (Arja Sadjiarto, 2000). Service satisfaction indicators are in need of benchmarks with values of honesty, responsibility, work motivation, commitment to serve the services provided to the community are very good, so for a good assessment for agencies, customer satisfaction forms a recommendation for the community to be happy with the service provided. very good (kirom, 2015, p. 13)